Genealogy of civil society: contemporary reinterpretation of the concept - Stojanović, Đorđe (Sociološki pregled, 2024)
Starting from the exceptional importance of civil society for political/democratic theory, the paper critically analyzes its position in various theoretical discourses, trying to detect the most current changes in its understanding. Along these lines, the paper examines the premodern, modern and postmodern paradigms of civil society. The most important findings are that its interpretation must include: (1) cultural procedurality and diversity against the abstract and repressive given of the Western matrix; (2) the fact that externally controlled non-genuine non-governmental organizations of neoliberal civil society have weak support from citizens and a low level of responsibility; (3) dialogue with neo-traditional associations; and (4) the idea that civil society cannot be freed in a utopian manner from the redistribution of power, which implies its politicization, hierarchization and civil society elites.